2018
DOI: 10.1111/dom.13531
|View full text |Cite
|
Sign up to set email alerts
|

Comparative risk of genital infections associated with sodium‐glucose co‐transporter‐2 inhibitors

Abstract: The extent to which sodium-glucose co-transporter-2 (SGLT2) inhibitors increase the risk of genital infections in routine clinical care, compared with other antidiabetic medications, is not clear, or whether the increased risk is consistent across gender or age subgroups, within individual SGLT2 agents, or if it is more pronounced at a particular time after treatment initiation. We conducted a retrospective cohort study using two US commercial claims databases (2013-2017). In the primary analysis, 1:1 propensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
88
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 20 publications
(40 reference statements)
9
88
0
10
Order By: Relevance
“…Nearly identical results have been found in observational studies (Table ) . For example, in the study by Dave et al, diagnostic codes specific to yeast infections caused by Candida were used and they observed a nearly threefold higher rate of genital infection among adults who received an SGLT2 …”
Section: An Overview Of Recent Literature Assessing the Risk Of Uti Wsupporting
confidence: 60%
See 2 more Smart Citations
“…Nearly identical results have been found in observational studies (Table ) . For example, in the study by Dave et al, diagnostic codes specific to yeast infections caused by Candida were used and they observed a nearly threefold higher rate of genital infection among adults who received an SGLT2 …”
Section: An Overview Of Recent Literature Assessing the Risk Of Uti Wsupporting
confidence: 60%
“…A recent meta‐analysis, including 56 clinical trials confirmed this observation, and found that SGLT2 inhibitors were associated with a threefold higher risk ratio [RR = 3.30, 95% confidence interval (CI) 2.74, 3.99, I 2 = 22%] for genital infection, regardless of sex, compared with placebo or other classes of diabetes medications . Nearly identical results have been found in observational studies (Table ) . For example, in the study by Dave et al, diagnostic codes specific to yeast infections caused by Candida were used and they observed a nearly threefold higher rate of genital infection among adults who received an SGLT2 …”
Section: An Overview Of Recent Literature Assessing the Risk Of Uti Wmentioning
confidence: 75%
See 1 more Smart Citation
“…In the phase 3 cardiovascular safety trials, genital infections occured with a 3‐ to 4‐fold increased incidence in patients receiving an SGLT2 inhibitor compared to placebo. A systematic analysis indicated a 3‐fold increased risk of developing a genital mycotic infection when receiving an SGLT2 inhibitor compared to other glucose lowering agents, with a similar incidence across individual SGLT2 inhibitors . A retrospective study of patients in a family practice setting indicated that SGLT2 inhibitors were associated with a more than 3‐fold increased risk of mycotic genital infections compared to patients receiving DPP4 inhibitors (2.9% vs 0.9%; HR 3.50; 95% CI: 1.95‐5.89).…”
Section: Adverse Effects Related To Either Blood Glucose Lowering Ormentioning
confidence: 99%
“…Given these data, is SGLT2i use actually associated with FG? Although SGLT2i are associated with genital fungal infections in both women and men, 16,17 none of the reviewed studies found an association between such superficial infections and FG, which, rather, was associated with procedures such as hemorrhoidectomy and with deep space infections, such as perianal 14 or vulvar abscess, 13 so a mechanism whereby SGLT2i may cause FG is not apparent. Certainly diabetes is present in many people with FG.…”
mentioning
confidence: 99%